LEXICOGRAPHY: SYNONYMS, ANTONYMS, AND HOMONYMS IN ENGLISH - Sara Jumabaeva; Aynura Seytbekova (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Lexicography, the science and practice of dictionary-making, plays a crucial role in describing and organizing the vocabulary of a language. Among its central concerns are semantic relationships such as synonymy, antonymy, and homonymy, which help users understand meaning, nuance, and usage. Synonyms are words that share similar meanings but often differ in connotation, register, or context, making their accurate representation essential for effective communication. Antonyms, by contrast, express opposite meanings and contribute to the structuring of semantic fields, enabling clearer distinctions between concepts. Homonyms, which are words that share the same form but have different meanings, present particular challenges in lexicography due to potential ambiguity and the need for precise definitions and contextual examples.This paper explores how modern English dictionaries classify and present these relationships, highlighting the importance of clear definitions, illustrative examples, and cross-references. It also examines the role of corpus linguistics and digital tools in improving the accuracy and usability of lexicographic resources. By analyzing synonyms, antonyms, and homonyms, the study demonstrates how lexicography supports language learning, translation, and effective communication, while also reflecting the dynamic and evolving nature of English vocabulary.